Does the Malaysian sovereign sukuk market offer portfolio diversification opportunities for global fixed-income investors? Evidence from wavelet coherence and multivariate-GARCH analyses - Bhuiyan, Rubaiyat Ahsan; Rahman, Maya Puspa; Saiti, Buerhan; Mat Ghani, Gairuzazmi (Elsevier Inc., 2019)
Understanding the co-movement among asset returns is a critical issue in finance, as investors can minimize risk through diversification. International investors seek alternative asset classes to diversify their portfolio. Therefore, it would be meaningful to investigate whether sukuk (Islamic bond) offer any advantages in terms of global diversification. In this context, we examined the volatilities and correlations of sovereign bond indexes in developed countries, such as the US, Canada, Germany, the UK, Australia, and Japan, and the Thomson Reuters BPA Malaysia Sukuk Index, using wavelet coherence and multivariate-GARCH analyses. The data cover the period January 2010–December 2015. The results of the study significantly highlight that wavelet coherence illustrates lower co-movement between returns on developed market bond index (the US, the UK, Australia, Canada, Germany, and Japan) with returns on the Malaysian sukuk index during the sample period. Moreover, the Malaysian sukuk market has negative unconditional correlation with the US and Canadian bond markets, which is a good sign of diversification benefits. This study reveals attractive opportunities in terms of diversification benefits, with credit quality and sharia-compliant financial sector exposure for investors who want to invest in fixed-income securities.